2010
DOI: 10.1002/glia.21034
|View full text |Cite
|
Sign up to set email alerts
|

RIG‐I mediates nonsegmented negative‐sense RNA virus‐induced inflammatory immune responses of primary human astrocytes

Abstract: While astrocytes produce key inflammatory mediators following exposure to neurotropic non-segmented negative-sense RNA viruses such as rabies virus and measles virus, the mechanisms by which resident central nervous system (CNS) cells perceive such viral challenges have not been defined. Recently, several cytosolic DExD/H box RNA helicases including retinoic acid-inducible gene I (RIG-I) have been described that function as intracellular sensors of replicative RNA viruses. Here, we demonstrate that primary hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 48 publications
4
70
1
Order By: Relevance
“…The involvement of (RLR) pathway in inflammatory cytokine production has been reported earlier in a few virus infection models such as astrocyte infection by vesicular stomatitis virus, neuronal infection by Japanese encephalitis virus, hepatic cell infection by HCV and endothelial cells infection by Dengue virus [45,46,47,48]. In CHIKV infected fibroblasts, the activation of RLR signalling pathway has been identified [49].…”
Section: Discussionmentioning
confidence: 91%
“…The involvement of (RLR) pathway in inflammatory cytokine production has been reported earlier in a few virus infection models such as astrocyte infection by vesicular stomatitis virus, neuronal infection by Japanese encephalitis virus, hepatic cell infection by HCV and endothelial cells infection by Dengue virus [45,46,47,48]. In CHIKV infected fibroblasts, the activation of RLR signalling pathway has been identified [49].…”
Section: Discussionmentioning
confidence: 91%
“…As such, these cells are ideally situated to detect and respond to invading pathogens including neurotropic viruses. Importantly, we have documented that microglia and astrocytes can be productively infected by VSV and respond by producing IL-6, TNF-α, and IL-1β(Chauhan et al, 2010; Furr et al, 2011, 2010), while earlier studies have demonstrated that these glial cells respond to VSV by proliferating, producing inducible NO synthase, and increasing the cell surface expression of MHC class II molecules (Bi et al, 1995), responses that are likely to set the stage for subsequent inflammatory damage.…”
Section: Neurotropism Of Vsvmentioning
confidence: 99%
“…PRR activation in astrocytes results in the expression of many immune mediators, including inflammatory cytokines and type I IFNs (12,13). During infection by pathoType I IFNs promote cellular responses to viruses, and IFN receptor (IFNAR) signaling regulates the responses of endothelial cells of the blood-brain barrier (BBB) during neurotropic viral infection.…”
Section: Introductionmentioning
confidence: 99%